2021
DOI: 10.1111/jace.17623
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties of Ca, Ti‐doped CeO2 and their influence on the reverse water‐gas shift reaction

Abstract: CeO2‐based materials can be found in a variety of catalytic processes, including the reverse water‐gas shift (RWGS) reaction. Nevertheless, the interaction of molecular gases with the surfaces of such materials is still not clear. Recently, some progress was reported on the incorporation of neodymium (Nd) and calcium (Ca) into ceria and their effect on H2O and CO2 adsorption. Titanium (Ti), which has a much smaller ionic radius, has the ability to change the interaction landscape, both as a co‐dopant to Ca and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Doping CeNPs with transition metals or rare earth metal such as Cu, Cr, Ti, Y, and La have been adopted as a promising approach to tune the catalytic activity of these materials. [326][327][328][329][330] The substitution process causes structural defects and creates more oxygen vacancies on the catalyst surface, which affects the generation and mobility of charged species such as electrons and oxygen anions. Furthermore, doped ceria can also tolerate high temperature annealing treatments due to the cooperative nature of the cations of the binary oxides.…”
Section: Catalysismentioning
confidence: 99%
“…Doping CeNPs with transition metals or rare earth metal such as Cu, Cr, Ti, Y, and La have been adopted as a promising approach to tune the catalytic activity of these materials. [326][327][328][329][330] The substitution process causes structural defects and creates more oxygen vacancies on the catalyst surface, which affects the generation and mobility of charged species such as electrons and oxygen anions. Furthermore, doped ceria can also tolerate high temperature annealing treatments due to the cooperative nature of the cations of the binary oxides.…”
Section: Catalysismentioning
confidence: 99%
“…Even after the loss of oxygen from the lattice and the consequent formation of numerous V O , CeO 2− x still retains a fluorite crystal structure [ 19 , 20 ] and captures oxygen by filling the V O upon exposure to oxygen, accompanied by the recovery of CeO 2 [ 21 ]. Moreover, the doping of other metallic elements into the CeO 2 lattice could control their structure and physical properties [ 22 , 23 , 24 ], such as rare–earth elements [ 25 , 26 , 27 ], transition elements [ 28 , 29 , 30 ] and alkaline earth elements [ 31 , 32 , 33 ]. In spite of the successful synthesis of CeO 2 –based composite oxides, most of the previous reports have focused on the investigation of catalytic performances [ 34 , 35 ], transport properties [ 36 , 37 ] and the origin of room–temperature ferromagnetism [ 38 , 39 ], the theoretical data about OSC were usually quite scattered, and only a few fundamental studies on the OSC of doped CeO 2 have been reported.…”
Section: Introductionmentioning
confidence: 99%